Impacts of training and aquaculture extension on livelihoods of rural fish farmers in different regions of Bangladesh (Dhaka University Journal of Biological Sciences, 2015)
This study was carried out to assess the impacts of aquaculture technologies training and extension adoption on the fish production and improvement of livelihoods of fish farmers. The research was conducted at five different areas of Bangladesh with 240 farmers. Of them half of the farmers were trained and the rest were non‐trained farmers. Among the trained farmers 86 were men and 34 were women. The mean fish production of the trained farmers (7.8 ± 2.2 kg/dec) was significantly higher (p < 0.01) fish production than that of the non‐trained farmers in the monitoring year (4.9 ± 1.7 kg/dec). There were differences in the fish production between the men and women trained farmers. For trained men farmers the fish production increased from 4.3 ± 1.3 to 8.2 ± 2.1 kg/dec and for women it increased from 3.8 ± 1.2 to 6.8 ± 2.1 kg/dec, respectively. The percentage increment in fish production of trained men farmers were 89 and women were 78 than their baseline year fish production. The outcomes showed that the training and extension support could increase fish production and livelihood significantly than that of the non‐trained farmers.Dhaka Univ. J. Biol. Sci. 24(1): 35-41, 2015 (January)